Low translational efficiency of the F1-ATPase beta-subunit mRNA largely accounts for the decreased ATPase content in brown adipose tissue mitochondria - Tvrdík, P; Kuzela, S; Houstĕk, J (FEBS letters, 1992)
The half-life of the F1-ATPase beta-subunit (F1-beta) mRNA in ATPase-poor brown adipose tissue (BAT) (t1/2 = 9.5 h) was found to be 3-7-fold shorter than in liver (t1/2 = 27 h) and heart (t1/2 = 63 h) of mice. When translated in reticulocyte lysate, a 2-3-fold lower efficiency appeared with F1-beta mRNA from BAT than from other tissues. The in vitro synthesized F1-beta protein precursors of BAT, liver and heart origin were imported and processed by mouse liver mitochondria with equal efficiency. The results indicate that the pool of abundant F1-beta mRNA in BAT is not fully translatable, most likely due to its low metabolic stability.
Keywords: messenger RNA; Mice, Inbred BALB C; Adipose Tissue, Brown; mitochondrie; Mitochondria, Liver; jaterní mitochondrie; posttranslační úpravy proteinů; Mice; proteosyntéza; Proton-Translocating ATPases; Protein Biosynthesis; proteinové prekurzory; Protein Precursors; myokard; zvířata; Protein Processing, Post-Translational; RNA, Messenger; Myocardium; protonové ATPasy; myši inbrední BALB C; northern blotting; myši; Mitochondria; Adenosine Triphosphatases; hnědá tuková tkáň; Blotting, Northern; adenosintrifosfatasy; Animals